Spark Parameter Monitoring Feedback System for Preparation of Nanosilver Colloid in EDM. Issue 2 (25th January 2016) - Tseng, Kuo-Hsiung; Chiu, Juei-Long; Lee, Heng-Lin; Kao, Yi-Syuan; Tien, Der-Chi
Abstract : This study developed a system monitoring the electric discharge machine's (EDM) discharge energy and success rate to replace conventional oscilloscope observation. By using logic circuit, the signals are transmitted to the PC monitoring platform in order to display the discharge success times, discharge success rate, and electrode's consumption energy. The advantage of the proposed system is the capability to observe real-time discharges and record the experimental conditions, as well as optimize the discharge parameter settings. The experimental results suggest that, in the preparation of nanosilver colloid, the cost-performance of Ton –Toff at 10–100 µs is the optimal setting. The monitoring system also can take advantage of the discharge success rate to control the energy consumption of the electrode to obtain the standardization of products. The results suggest that, while discharge success rate, electrode's weight loss and wavelength of the absorption peak are considerably accurate, but concentration accuracy is relatively poor. The discharge success rate monitoring system is an innovative method that can help to realize electric discharge processing, optimize product quality, and it may be a powerful processing tool in the future.